2005
DOI: 10.1007/s00248-004-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Tomato Root Seedling by Pseudomonas fluorescens 92rkG5: Spatio–temporal Dynamics, Localization, Organization, Viability, and Culturability

Abstract: The localization, viability, and culturability of Pseudomonas fluorescens 92 rkG5 were analyzed on three morphological root zones (root tip + elongation, root hair, and collar) of 3-, 5-, and 7-day-old tomato plants. Qualitative information about the localization and viability was collected by confocal laser scanning microscopy. Quantitative data concerning the distribution, viability, and culturability were obtained through combined dilution plating and flow cytometry. Colonization by P. fluorescens affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Advances in molecular techniques, fluorescence labeling, and imaging such as confocal laser microscopy, may be useful in the future. These techniques have been used to study colonization of roots by biocontrol bacteria and fungi (Gamalero et al 2005;Bloemberg et al 2000;Lu et al 2004) and infection of roots by Fusarium (Lagopodi et al 2002;Bolwerk et al 2005;Olivain et al 2006), but these have been descriptive and have not employed spatial statistics.…”
Section: Spatial Aspects Of Soilborne Pathogens and Root Diseasesmentioning
confidence: 99%
“…Advances in molecular techniques, fluorescence labeling, and imaging such as confocal laser microscopy, may be useful in the future. These techniques have been used to study colonization of roots by biocontrol bacteria and fungi (Gamalero et al 2005;Bloemberg et al 2000;Lu et al 2004) and infection of roots by Fusarium (Lagopodi et al 2002;Bolwerk et al 2005;Olivain et al 2006), but these have been descriptive and have not employed spatial statistics.…”
Section: Spatial Aspects Of Soilborne Pathogens and Root Diseasesmentioning
confidence: 99%
“…For example, some rhizosphere-restricted bacteria as well as some endophytes have been detected on and/or inside plants as VBNC cells (Hurek et al, 2002;Gamalero et al, 2004Gamalero et al, , 2005, but it is currently unknown why cells switch to this state. Switching to a VBNC state on and inside plants might indicate that bacteria experience stress during host colonization, but this phenomenon is still poorly understood.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…High bacterial abundance was found on the root tips 11,[13][14][15] and at root branching zones. 13 Yet other studies reported an absence or scarcity of bacterial colonisation at the root tips [16][17][18][19][20] perhaps caused by the high turnover of mucilage and border cells at the root apex. 20 It is likely that the choice of the technique used to determine bacterial numbers along the root has a strong influence on bacterial count estimates.…”
mentioning
confidence: 99%